The Effect of Pre-emptive Dose of Dexamethasone on Pain, Nausea, Frequency of Vomiting, and Postoperative Restlessness in Patients Undergoing Septorhinoplasty: A Randomized Control Clinical Trial Study - Parvin Sajedi; Amir Mohammad Travati (Advanced Biomedical Research)
Background: This study was conducted with the aim of determining the effect of pre-emptive dose of dexamethasone on pain, nausea, frequency of vomiting, and restlessness after septorhinoplasty. Materials and Methods: In this clinical trial study, 70 patients’ candidates for septorhinoplasty were divided into two groups of 35 and before induction of anesthesia, 0.1 mg/kg of dexamethasone was injected intravenously in the first group and the same volume of normal saline in the second group. Postoperative nausea severity and frequency of vomiting, pain intensity, patient restlessness, painkiller, and antinausea medication usage up to 24 hours after surgery were evaluated and compared in two groups. Results: There was a significant difference between the two groups in the mean of pain intensity at the time of recovery (0.031). Also, 6 hours (P = 0.016), 12 hours (P=<0.001), 18 hours (P = 0.013), and 24 (P = 0.009) hours after the operation, the control group had higher pain intensity. In recovery, 9 (28.1%) of the dexamethasone group and 22 (66.7%) of the control group had restlessness (P = 0.002). Severity of nausea from PACU until 24 hours after surgery showed that the dexamethasone group had less nausea at the PACU (P ˂ 0.001); three subjects from this group have vomited and seven subjects from the control group vomited after surgery, and differences were not significant (P = 0.3). Conclusion: Intravenous dexamethasone 0.1 mg/kg before induction of anesthesia reduced the intensity of pain, nausea, restlessness, and the need for painkillers and antinausea drugs, without causing serious hemodynamic disorders. It seems that the use of this drug with the mentioned dose in septorinoplasty patients is associated with a reduction in postoperative complications.